Performance Analysis of Cognitive Radio System Based on Outage Probability of Cognitive Transmission - Haomin Gao; Haifeng Zhao; Xiao Liang; Xiaomin Mu (Dianxin kexue)
It is an important part to design an optimal spectrum sensing and transmission framework in cognitive radio network.Considering that cognitive data transmission outage had effect on the performance of cognitive radio system,a novel spectrum sensing and transmission model based on the outage probability of cognitive transmission was proposed and the two phases of spectrum sensing and data transmission were jointly optimized.The model was formulated as a nonconvex optimization problem under the constraint of interference to primary user,which maximized the average achievable throughput by the joint optimization of sensing time and data transmission rate and simulated by means of the numerical method.The numerical analysis shows that a better tradeoff can be achieved among the protection of primary user,the throughput of cognitive system and transmission delay when the outage probability is cited and the constraint is satisfied.